2021
DOI: 10.3390/ani11020390
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Phase Biometric Relationships and Sexual Maturity in the Atlantic Bluefin Tuna, Thunnus thynnus (Osteichthyes: Scombridae)

Abstract: Most fish undergo distinct growth phases during ontogenesis. An extremely important passage from the juvenile to adult phase occurs at the onset of sexual maturity, which shows in body proportion and/or growth rate changes. These can be detected as change-points in biometric relationships. In this paper, the Atlantic bluefin tuna was analyzed to verify whether its somatic proportions show any sign of discontinuity during growth, i.e., whether any change-points may be detected in its somatic proportions. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…However, it is widely reported that the Atlantic cod may not spawn annually once reaching maturation (Rideout et al., 2000 and references therein cited). Electronic tagging experiments and fishery data have shown that not all the adult individuals of the highly migratory species Atlantic bluefin tuna visit any of the known spawning grounds during the spawning season, thus leading to the disputed hypothesis that only a fraction of the adult population contributes to recruitment (Bello et al., 2021 ; Corriero et al., 2020 ; Medina, 2020 ), a reproductive strategy that could involve follicular atresia as mechanism underlying spawning omission.…”
Section: Ecological Aspects and Impact Of Atresia On Fish Reproductive Potentialmentioning
confidence: 99%
“…However, it is widely reported that the Atlantic cod may not spawn annually once reaching maturation (Rideout et al., 2000 and references therein cited). Electronic tagging experiments and fishery data have shown that not all the adult individuals of the highly migratory species Atlantic bluefin tuna visit any of the known spawning grounds during the spawning season, thus leading to the disputed hypothesis that only a fraction of the adult population contributes to recruitment (Bello et al., 2021 ; Corriero et al., 2020 ; Medina, 2020 ), a reproductive strategy that could involve follicular atresia as mechanism underlying spawning omission.…”
Section: Ecological Aspects and Impact Of Atresia On Fish Reproductive Potentialmentioning
confidence: 99%